2008
DOI: 10.1063/1.2830964
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic analysis of current driven domain wall motion in nanostrips with perpendicular magnetic anisotropy

Abstract: Current driven domain wall motion in nanostrips with perpendicular magnetic anisotropy was analyzed by using micromagnetic simulation. The threshold current density of perpendicular anisotropy strips in adiabatic approximation was much smaller than that of in-plane anisotropy strips, and it reduced with thickness reduction. The differences originate from the differences in domain wall width and hard-axis anisotropy. Also, the threshold current density of perpendicular anisotropy strips required to depin from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
113
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 19 publications
(16 reference statements)
6
113
0
1
Order By: Relevance
“…For the case, where the deviations are non-negligible an additional torque is introduced in the M × (p 0 · V)M direction, which is referred to as the non-adiabatic torque. The narrow (few nanometres wide) DWs in nanowires with very large PMA are the reason for their high sensitivity to spin-polarized currents [30]. But there is still a debate in the theoretical description of current-induced DW motion on how to describe the damping and whether there is an additional torque in the direction of the non-adiabatic torque [44,48], which arises from the same processes that contribute to magnetic damping.…”
Section: Underlying Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…For the case, where the deviations are non-negligible an additional torque is introduced in the M × (p 0 · V)M direction, which is referred to as the non-adiabatic torque. The narrow (few nanometres wide) DWs in nanowires with very large PMA are the reason for their high sensitivity to spin-polarized currents [30]. But there is still a debate in the theoretical description of current-induced DW motion on how to describe the damping and whether there is an additional torque in the direction of the non-adiabatic torque [44,48], which arises from the same processes that contribute to magnetic damping.…”
Section: Underlying Theorymentioning
confidence: 99%
“…This approach offers highly efficient, unidirectional DW motion independent of the adjacent magnetic domain configuration. While DW motion under applied fields is relatively slow in nanowires with PMA, current-induced motion in these materials can be relatively fast and efficient [30]. Controlling DW position under spinpolarized currents and/or with PMA materials can be achieved using pinning from geometric features [2,12,31,32].…”
Section: Basic Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] Recent studies on materials with perpendicular anisotropy have revealed a higher efficiency for CIDM than in the case of in-plane magnetized materials. [8][9][10][11] Especially the contributions of the adiabatic 12,13 and nonadiabatic spin torque due to spin relaxation [14][15][16] or momentum transfer 12,14 to the domain wall ͑DW͒ motion and their dependence on the material properties are so far not fully understood. In particular, studies on Co/Pt multilayers show a large nonadiabaticity factor ␤.…”
mentioning
confidence: 99%
“…Spin current induces magnetization dynamics, i.e., spin-transfer-torque [2][3][4][5], which has been extensively studied through current-induced domain wall (DW) motion, primarily in permalloy (NiFe) nanowires with in-plane magnetization [6][7][8][9][10]. Recently, it has been reported experimentally [11,12] and theoretically [13,14] that nanowires with perpendicular magnetic anisotropy (PMA) are more favorable for spin-transfer-torque devices because they exhibit DW motion at a lower threshold current. On the other hand, the same interaction mediates energy-transfer from magnetization into conduction electrons, i.e., spinmotive force (SMF) [15].…”
mentioning
confidence: 99%